Adult Work Commitment, Financial Stability, and Social Environment as Related to Trajectories of Marijuana Use Beginning in Adolescence. Issue 3 (July 2013) - Brook, Judith S.; Lee, Jung Yeon; Finch, Stephen J.; Seltzer, Nathan; Brook, David W.
Background: The objective of this study is to examine trajectories of marijuana use among African Americans and Puerto Ricans from adolescence to adulthood, with attention paid to work commitment, financial stability, drug use, and violence. Methods: Participants ( N = 816) completed in-class questionnaires as students in the East Harlem area of New York City at the first wave and provided follow-up data at 4 additional points in time (mean ages = 14, 19, 24, 29, and 32 years). Among 816 participants, there were 60% females, 52% African American, and 48% Puerto Ricans. Results: The chronic marijuana user trajectory group compared with the none or low, increasing, and/or moderate marijuana user trajectory group was associated with negative aspects of work commitment, financial stability, and the social environment. The chronic marijuana user group was similar to the increasing marijuana user group on work commitment and financial stability. Conclusions: These results suggest that treating marijuana use in late adolescence may reduce difficulty in the assumption of adult roles. Because chronic marijuana users experienced the most adverse effects in each of the domains, they require more intense clinical intervention than moderate marijuana users.